Numerical modelling of composite laminates with through-thickness-reinforcements - Grassi, Marcello (Cranfield University, 2004)
The main objective of the present research study was to develop numerical models to investigate the mechanical properties and effectiveness of z-fibre reinforced laminates. A survey of relevant literature on through-thickness reinforcements (TTR) was undertaken and z-fibre pinning was chosen as the main topic of study. The development of numerical tools was mainly based on the finite element (FE) method and was carried out at different model scale levels. At a micro-mechanical level of analysis, two models were presented. Firstly a unit cell FE model based on the actual geometric configuration of a z-pinned composite was used. Calculations were performed to understand how the through-thickness reinforcement modified the engineering elastic constants and local stress distributions. Secondly the study of an analytical micro-mechanical model was undertaken. The model simulated a z-fibre bridging a delamination crack tinder mixed-mode loads. A constitutive law relating the z-pin bridging forces with the crack displacements was defined as the "bridging law". Numerical examples for z-fibre bridging laws under Mode I and Mode II loads were computed along with design evaluations of the effect of several micro-mechanical parameters on the bridging laws. This analytical model was then implemented into a MATLAB code specifically written by the author. The code generated constitutive relationship for interface elements simulating the bridging laws of a single z-pin to be used in a FE analysis. A detailed numerical study of the mode I interlaminar fracture of composite laminates with z-pins was then carried out. AFL• model of a double cantilever beam (DCB) was developed. The numerical analysis focused on the large scale bridging (LSB) caused by z-pins mechanics, which increased the laminate resistance against delamination growth. The numerical results were validated against experimental data. Computational curves for the energy balance and energy rates were also determined showing that the LSB process consumed a significant amount of irreversible energy. The assumption made by the linear elastic fracture mechanics (LEFM) that all energy dissipations were included in the fracture energy and confined within the damage front, was not valid for z-pinned laminates. The FE analysis was then extended to study a curved single-lap shear joint, to prove the effectiveness of TTR against debond failure of the joint. The presence of TTR was shown to delay the propagation of the debonding and generally to enhance the load carrying capability of the joint. TTR is proved to be more effective in reducing the Mode I component of debonding driving force than that of the Mode II. Finally a global-local approach was proposed to implement the TTR elements into large composite stnictural FE models. Possible future studies for TTR numerical modelling were also addressed.